1337 Investigating the effectiveness of organisationallevel interventions for the management of work-related stress through a process evaluation: an italian case study. (24th April 2018) - Di Tecco, C; Ronchetti, M; Ghelli, M; Persechino, B; Iavicoli, S
Abstract : Introduction: Evaluating the effects of organisational level interventions, as those related to work related-stress, is broadly recognised crucial to identify the key steps needed to ensure the efficacy of interventions. The Italian Workers' Compensation Authority (INAIL) developed a methodology for management of risks associated to work related-stress as an organisational integrated approach useful for OSH professional and companies. This study provides a process evaluation of organizational-level work related stress management interventions in a public administration using the INAIL's methodology. Methods: An Italian Public Administration (more than 4, 000 employees) has carried out a process of risk assessment and management of work-related stress using the INAIL's approach and tools, with the methodological support of a research team form INAIL. Our support ensured that some key aspects of the process were implemented such as: specific training, the active involvement of workers, and OSH professionals, and raise the awareness of management on the importance of organisational level interventions in managing stress at work. According to the literature, we analysed intervention process using two methodological approaches: quantitative and qualitative. Results: Some aspects resulted valuable for the effectiveness of the interventions: the active role played by OSH professionals in implementing the process; 2) the high participation of workers with a 75% of response rate in the risk assessment (3200 questionnaires); 3) The direct involvement of the management; 4) a bottom-up approach through the active involvement of workers by the means of focus groups in identifying concrete actions based on the assessment findings in collaboration with OSH professional and managers. Discussion: This study investigates the ways of implementing an effective integrated approach for assessing and managing work related stress using the INAIL's methodology through a process evaluation of organizational-level interventions. Findings contributes to the international debate on how to verify the effectiveness of processes of intervention planning and implementation.